Отморозки, или Грязная жизнь: [роман] / Владимир Колычев - Колычев Владимир Григорьевич (Мастер криминальной интриги, 2012)
Экземпляры: Ф. 12 (20210503) / Инвентарный номер: 48367 / Цена: 45.00 / Сис.шифр: 84(2=411.2)6-44 / Авт.знак: К 60 / ГРНТИ: 17.82.31 / ББК: 84(2=411.2)6-44